PENGARUH KEMUDAHAN PENGGUNAAN, HARGA DAN KEPERCAYAAN TERHADAP MINAT BELI PADA SITUS BELANJA ONLINE LAZADA (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Riau) - Pratama Eko; Wijayanto Gatot; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to determine the effect of Ease to Use, Price and Trust in Buying Interest on the Lazada online shop site among students. The population in this study were all students of the Faculty of Economics and Business, University of Riau who used the Lazada application and the samples taken were 100 people. To test the hypothesis in this study is to use multiple linear analysis with the help of SPSS.17 program.The results of the study show that: 1) Ease of Use has a positive but not significant effect on Buying Interest on Lazada's online shopping site, 2) Price has a positive but not significant effect on Buying Interest on Lazada's online shopping site, 3) Trust has a positive and significant effect on buying interest on Lazada's online shopping site. 4) Simultaneously Ease of Use, Price and Trust has an affect of Buying Interest on the Lazada online shopping site.Keywords: Ease to Use, Price, Trust and Buying Interest